DIFFERENTIATION IN MUSICAL EDUCATION - Éva PÉTER (Studia Universitatis Babeş-Bolyai. Musica)
The contemporary pedagogic view takes into consideration the varied skills the various pupils have. Therefore it considers that the teaching material and the methods used in musical education need to be established having in view the abilities and level of development of each individual to be educated. In the following I will present factors that make differentiation in musical education necessary, respectively the classical local methods and new foreign methods by which differentiation in musical education can be achieved.